2020
DOI: 10.25080/majora-342d178e-013
|View full text |Cite
|
Sign up to set email alerts
|

Leading magnetic fusion energy science into the big-and-fast data lane

Abstract: We present Delta, a Python framework that connects magnetic fusion experiments to high-performance computing (HPC) facilities in order leverage advanced data analysis for near real-time decisions. Using the ADIOS I/O framework, Delta streams measurement data with over 300 MByte/sec from a remote experimental site in Korea to Cori, a Cray XC-40 supercomputer at the National Energy Energy Research Scientific Computing Centre in California. There Delta dispatches cython data analysis kernels using an mpi4py PoolE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…We continue by evaluating the performance of computational kernels implementing equation (1). Previous work showed that kernels which implement equation (1) for central processing units (CPUs) can utilize multithreading and scale linearly with the numbers of threads [32]. In this work we utilize a kernel, labeled GAP, that fuses calculations of equations (1a)-(1c) for a given channel pari (X, Y) and runs on GPUs.…”
Section: Individual Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…We continue by evaluating the performance of computational kernels implementing equation (1). Previous work showed that kernels which implement equation (1) for central processing units (CPUs) can utilize multithreading and scale linearly with the numbers of threads [32]. In this work we utilize a kernel, labeled GAP, that fuses calculations of equations (1a)-(1c) for a given channel pari (X, Y) and runs on GPUs.…”
Section: Individual Componentsmentioning
confidence: 99%
“…In this paper, we present a streaming data analysis framework that aims to connect fusion experiments with remote HPC resources [2,6,19,32]. The streaming paradigm implemented by this framework allows the data generated by fusion experiments to be seamlessly analyzed using supercomputers as they are generated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In modern practice, the following situation began to arise. A series of full-scale experiments is being carried out at the facility and in order to make a decision on the next step of the experiment, it is necessary to quickly process the current results [26]. The necessary processing speed can be provided by supercomputer technologies, whereas the program running in such a situation should not be run in batch mode, however it should be run online in order to respond and process data quickly.…”
Section: Systems Analysis Of Visualization Systemsmentioning
confidence: 99%
“…The necessary processing speed can be provided by supercomputer technologies, whereas the program running in such a situation should not be run in batch mode, however it should be run online in order to respond and process data quickly. In practice, it even happens that the facility is located in one part of the planet but the supercomputer is located in another [26].…”
Section: Systems Analysis Of Visualization Systemsmentioning
confidence: 99%